Surname match/mismatch revisited: It may no longer matter for partner choice - Takefumi Nakazawa; Naoto Shinohara; Yuya Fukano (PLoS ONE, 2026)
Kin recognition plays a crucial role in mating across various biological taxa, including bacteria, plants, and animals, to prevent inbreeding. Historically, surnames have been indicators of kinship in humans, with many countries enforcing laws and norms to prohibit marriages between individuals sharing the same surname in the past. Here, considering the potentially adaptive role of surname mismatch in inbreeding avoidance, we address whether surnames can still influence partner choice in modern human society, where same-surname marriages are no longer prohibited, by utilizing nation-wide name databases from Taiwan. Analysis of data from 2018 revealed a lower frequency of same-surname marriages than expected, reflecting historical taboos against such marriages. However, this pattern was not observed in the 2023 data, suggesting a potential shift in people’s attitudes over time. To further interpret this trend, we conducted a simple questionnaire survey among university students, which showed no significant correlation between surname coincidence and attractiveness ratings of heterosexual face images, in contrast to the traditional custom. Our results, although preliminary, suggest the hypothesis that the significance of surname match/mismatch in partner choice may have diminished, potentially due to rapidly changing socio-cultural environments. Further research into the shifting role of surnames is necessary to gain a deeper understanding of human social behaviors across different regions and contexts amidst modernization and globalization.